The Impact of Divergent and Convergent Tasks on Iraqi EFL Students Reading Comprehension Success - Sabeeha Hamza Dehham; Nadia Majeed Hussein (Universitas Muhammadiyah Metro, 2021)
This research attempted to explore the effects of divergent and convergent tasks on the successful reading of EFL students at the preparatory stage. To verify the analysis, the null hypothesis was established that states